Noise prediction and measurement from construction sites - Darus, Nadirah (2014)
Construction industry is one of the contributors to economic growth and it has the highest tendency to generate noise. Construction noise becomes one of the main sources of noise pollution which affect the public and construction workers. Construction noise prediction at planning stage must be carried out and prepared through Environmental Impact Assessment (EIA). There are various methods of construction noise prediction that have been practiced by the respected parties. The British Standards Institution (BSI) and the Department of Environment (DOE) have published BS 5228 – Part 1: 2009 – Code of Practice for Noise and Vibration Control on Construction and Open Sites and The Planning Guidelines for Environmental Noise Limits and Control respectively. These standards and guidelines were usually be used by the respected parties since currently, there are no specific established noise prediction method. However, previous researches were claimed BS 5228 – Part 1: 2009 procedures as inaccurate due to several factors. Thus, this study was carried out to evaluate the disparity of results between construction noise predictions using BS 5228 – Part 1: 2009 procedures and real on-site noise measurements. The objectives of this study are to obtain noise levels from construction sites, to predict noise levels from construction sites and to evaluate the disparity between these two results. The real on-site noise measurements were conducted at three selected construction sites with different stages of construction. Meanwhile, construction noise predictions were calculated using BS 5228 – Part 1: 2009 procedures. The disparity of the results was evaluated using statistical test in Statistical Package for Social Sciences (SPSS) software. The results of one sample T-test show the significant differences between these two results. The disparity might due to several affecting factors such as atmospheric and geometrical factors, operation conditions, periods and powers and work schedules of construction activities.